2019
DOI: 10.1590/1516-3180.2018.0293240119
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment using the lipid accumulation product index among primary healthcare users: a cross-sectional study

Abstract: BACKGROUND: The lipid accumulation product (LAP) index is an abdominal adiposity marker. OBJECTIVE: The aim of this study was to describe the cardiovascular risk of primary healthcare users through the LAP index and correlate it with anthropometric and biochemical indicators. DESIGN AND SETTING: Cross-sectional study in primary care units in a city in northeastern Brazil. METHODS: The subjects responded to a structured questionnaire that contained questions about their sociodemographic condition, and then unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Studies have shown that it is significantly correlated with cardiovascular risk and metabolic syndrome [8], and similar studies have been conducted on active acromegaly patients [9,10]. Lipid accumulation product (LAP) is calculated based on the measurement of serum TG levels and WC [11], and has been used to predict cardiovascular risk in different disease populations (type 2 diabetes mellitus, insulin resistance, polycystic ovary syndrome) [12]. The plasma atherogenic index (PAI), is calculated using plasma TG and C levels, and studies have shown it to be an important indicator of atherosclerosis and coronary artery disease [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it is significantly correlated with cardiovascular risk and metabolic syndrome [8], and similar studies have been conducted on active acromegaly patients [9,10]. Lipid accumulation product (LAP) is calculated based on the measurement of serum TG levels and WC [11], and has been used to predict cardiovascular risk in different disease populations (type 2 diabetes mellitus, insulin resistance, polycystic ovary syndrome) [12]. The plasma atherogenic index (PAI), is calculated using plasma TG and C levels, and studies have shown it to be an important indicator of atherosclerosis and coronary artery disease [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the identi ed cutoff value of LAP was 33.54 (sensitivity, 54.6%; speci city, 62.42%) in study population, a number of studies have found similar results. A study in northeastern Brail showed that the cutoff value of LAP index to present a higher chance of cardiovascular risk was 37.9 [49], an investigation conducted among Urumqi in China found that LAP was better than BMI to predict cardiovascular risk and the predictive accuracy was 38.41 in 215,651 adults [29]. Meanwhile, in southern Taiwan, China, Chiang et al [50] evaluated that the optimal cutoff value for the LAP index to predict diabetes was 28.4.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) is the recommended indicator to assess and diagnose obesity [11][12], but there is increasing evidence indicating that BMI is not the ideal body fat index [13], it has limitation to differentiate fat and muscle mass and can not re ect central obesity. A research conducted in America showed that 33% of elderly adults at a normal weight de ned by BMI have pre-diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Kahn proposed the concept of lipid accumulation product (LAP) at the beginning of twenty-first century, and the lipid accumulation index has been used as a marker of the degree of abdominal obesity based on the ratio of waist circumference (WC) and triglyceride (TG) content [ 5 ], and it was calculated as (WC−60.6) × (TG [mmol/L]) in males and (WC−54.1) × (TG [mmol/L]) in females based on the findings from Shanghai Chinese population. In addition, LAP has been found to be also closely related to type 2 diabetes [ 6 ], cardiovascular diseases [ 7 ], hypertension [ 8 ], and ovarian syndrome [ 9 ]. LAP may be better to predict the risk of a disease according to the fat content and distribution.…”
Section: Introductionmentioning
confidence: 99%